Designers against aids : the first decade! - De Botton, Alain; Murk, Ninette; Murk, Ninette; O'Brien, Michael James ([Antwerpen] : Ludion, 2010)
This book looks back on DAA's first decade, its past initiatives and campaigns, covering all the highlights, and with contributions by former director of UNAIDS Peter Piot, philosopher and writer Alain de Botton and of course Ninette Murk, founder of DAA and mother organization Beauty without Irony. By buying the book, you also contribute financially to the building of a new Education Center in Antwerp, where people from all over the world will be trained to raise awareness (and funds) against AIDS.
boek